Cryptic speciation associated with geographic and ecological divergence in two Amazonian Heliconius butterflies. Issue 1 (4th August 2018) - Rosser, Neil; Freitas, André V L; Huertas, Blanca; Joron, Mathieu; Lamas, Gerardo; Mérot, Claire; Simpson, Fraser; Willmott, Keith R; Mallet, James; Dasmahapatra, Kanchon K
Abstract: The evolution of reproductive isolation via a switch in mimetic wing coloration has become the paradigm for speciation in aposematic Heliconius butterflies. Here, we provide a counterexample to this, by documenting two cryptic species within the taxon formerly considered Heliconius demeter Staudinger, 1897. Amplified fragment length polymorphisms identify two sympatric genotypic clusters in northern Peru, corresponding to subspecies Heliconius demeter ucayalensis H. Holzinger & R. Holzinger, 1975 and Heliconius demeter joroni ssp. nov. These subspecies are reciprocally monophyletic for the mitochondrial genes COI and COII and the nuclear gene Ef1α, and exhibit marked differences in larval morphology and host plant use. COI sequences from 13 of the 15 currently recognized subspecies show that mtDNA differences are reflected across the range of H. demeter, with a deep phylogenetic split between the southern and northern Amazonian races. As such, our data suggest vicariant speciation driven by disruptive selection for larval performance on different host plants. We raise Heliconius demeter eratosignis (Joicey & Talbot, 1925) to Heliconius eratosignis based on nomenclatural priority, a species also comprising H. eratosignis ucayalensis comb. nov. and three other southern Amazonian races. Heliconius demeter joroni spp. nov. remains within H. demeter s.s., along with northern Amazonian and Guianan subspecies.